2017
DOI: 10.3389/fpls.2017.00261
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analysis Reveals Mechanisms of Sterile and Fertile Flower Differentiation and Development in Viburnum macrocephalum f. keteleeri

Abstract: Sterile and fertile flowers are an important evolutionary developmental (evo-devo) phenotype in angiosperm flowers, playing important roles in pollinator attraction and sexual reproductive success. However, the gene regulatory mechanisms underlying fertile and sterile flower differentiation and development remain largely unknown. Viburnum macrocephalum f. keteleeri, which possesses fertile and sterile flowers in a single inflorescence, is a useful candidate species for investigating the regulatory networks in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Cytological observation showed that C. oleifera pollen tube growth inhibition ( Figure 1) after self-pollination is PCD-related [33]. Twenty putative PCD-related genes (10 positive and 10 negative) from literatures [46][47][48][49][50][51] were identified. In Table S5, we can find that 73 PCD-related transcripts were expressed in mature pollen at lower levels than those in self-, cross-and non-pollinated pistils.…”
Section: Identification Of Pcd Candidate Transcriptsin Self-and Crossmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytological observation showed that C. oleifera pollen tube growth inhibition ( Figure 1) after self-pollination is PCD-related [33]. Twenty putative PCD-related genes (10 positive and 10 negative) from literatures [46][47][48][49][50][51] were identified. In Table S5, we can find that 73 PCD-related transcripts were expressed in mature pollen at lower levels than those in self-, cross-and non-pollinated pistils.…”
Section: Identification Of Pcd Candidate Transcriptsin Self-and Crossmentioning
confidence: 99%
“…PCD could be controlled by both positive and negative regulators. In this study, 20 putative key PCD-related genes were detected based on their expression patterns, which included 10 positive genes (ADHIII, AMC4, CAT2, CRY1, RING1, RSP, POB1, SRC2, UBA2C and XCP1) and 10 negative genes (ACA4, BON3, CBSX5, CNX1, CRLK2, IMPA4, P2C63, RBOHA and VPS45) [46][47][48][49][50][51] (Table S5). Most of the positive genes exhibited relatively high levels of expression in SP by Duncan's test, such as CAT2, CRY1, RING1, RSP and UBA2C ( Figure 5A).…”
Section: Pcd-regulated Genes Regulate the Inhibition Of Pollen Tube Imentioning
confidence: 99%
“…Sequencing libraries were generated using the NEBNext Ultra RNA Library Prep Kit for Illumina (New England Biolabs, Ipswich, MA, USA) in accordance with the manufacturer's instructions, and mRNA was purified from total RNA using poly-T oligo-attached magnetic beads. cDNA synthesis was subsequently performed as described previously [21]. RNA sequencing was performed on the Illumina Hiseq 4000 platform.…”
Section: Rna Isolation and Illumina Sequencingmentioning
confidence: 99%
“…Our transcriptomic analysis showed that many transcription factors exhibit dynamic gene expression changes in V . macrocephalum f. keteleeri flowers [ 23 ], and some of these genes are miRNA targets. A total of 190 targets of known miRNAs were predicted and annotated with gene descriptions.…”
Section: Discussionmentioning
confidence: 99%
“…After quality control and removing tags from these sources, mapped sRNA tags were used to look for known and novel miRNAs. The sRNA annotation process was performed as follows: 1) The sRNA tags were first mapped to the reference sequence (our transcriptome data sets NCBI SRA [SRP076665] and GEO [GSE83429]) using Bowtie [ 22 , 23 ], without allowing any mismatches, to analyze their expression and distribution relative to the reference sequence. 2) Next, the mapped sRNA tags were used to search for known miRNAs using a modification of the miRDeep2 program (with miRBase used as the reference).…”
Section: Methodsmentioning
confidence: 99%